CORRELATION BETWEEN MAMMOGRAPHY AND ULTRASOUND IN BREAST CANCER - Aviño, J. (2015)
We report our experience with 95 cases of breast carcinoma, operated during the years 1983-1985, to which was performed as exploratory methodical, among others, an ultrasound and a mammogram. The images are described, both mammography and ultrasound, we have found. In mammography screening, we obtained a 12.63% false negative, which then corresponded to carcinomas in stages T1 and T2. We study the correlation with other exploration techniques. Ultrasound there was a 21.05% false negative. The importance of mammography is valued more accurate method, although advising be supplemented with other diagnostic methods.